A Comparative Study Of Some Physical And Functional Variables Between Judo and Freestyle Wrestlers Of The Ages 15 – 16 years - عبد الله حمد السلامي أسعد (Journal of Physical Education, 2019)
Physical and functional variables have great importance on improving performance and the achievement of wrestlers in judo and in freestyle wrestling. The problem of the study was that judo and freestyle wrestlers should have special physical and functional variables and they should not confuse them with each other whoever similar they may seem. The aim of the research is to identify the correlation between some physical and functional variables of judo and freestyle wrestling. He also aims at identifying the direction of this correlation for every ability understudy. The researcher hypothesized that there is a random non statistical correlation between physical and functional abilities of both sports judo and freestyle wrestling. In addition to that, he hypothesized that there is a one direction correlation for each of the physical and functional abilities understudy. The researcher used the descriptive method. The tests were selected and conducted on (18) judo and freestyle wrestlers of the ages 15 – 16 years. The researcher conducted a pilot study on (6) wrestlers three for each type of wrestling. The results showed that there is a random non statistical correlation as well as a significant statistical correlation between physical and functional variables for both judo and freestyle wrestling. The researcher concluded that there is a random non statistical correlation for most variables understudy yet there were also significant correlation in one variable. Finally he recommended paying attention to these variables and their important role in all types of wrestling.